Utilization Of The Environment Around The School As A Learning Medium To Increase Interest And Achievement In Learning Natural Science - Fatimah, Siti (Universitas Sebelas Maret, 2022)
Learning is something that is very important for students. A sign that student learning is effective is achievement, learning achievement shows the ability of students to follow the learning program in a certain time. In achieving learning achievement, one of the influencing factors is interest in learning. The higher a person's interest in teaching and learning activities, the stronger the attention to these activities. This study aims to determine whether the utilization of the environment around the school as a learning medium can increase interest and achievement in learning science about fourth grade students of SD Negeri 1 Kadilanggon The hypothesis proposed in this study is the utilization of the environment around the school as a learning medium to increase motivation and achievement in learning science in fourth grade students of SD Negeri 1 Kadilanggon. Data in this study were collected by conducting process observations and interviews with students. While learning achievement data is collected by taking the average score of science subjects. The conclusion based on the results of research and discussion, namely the utilization of the environment around the school as a learning medium to increase motivation and achievement in science learning in grade IV students of SD Negeri 1 Kadilanggon.